Air Freight : A Market Study with Implications for Landlocked Countries - World Bank (Washington, DC, 2014)
To facilitate air freight, landlocked countries need to improve operations at their airports and liberalize access for foreign airlines. But until those countries become major exporters, it is unlikely that scheduled air cargo operators will have significant operations. Instead, most air cargo will move as belly cargo on passenger airlines, with some complementary use of chartered air freighters during shipment peaks. Landlocked countries should therefore provide greater access to foreign passenger airlines.